2021
DOI: 10.1038/s41368-021-00147-z
|View full text |Cite
|
Sign up to set email alerts
|

Advances in biomineralization-inspired materials for hard tissue repair

Abstract: Biomineralization is the process by which organisms form mineralized tissues with hierarchical structures and excellent properties, including the bones and teeth in vertebrates. The underlying mechanisms and pathways of biomineralization provide inspiration for designing and constructing materials to repair hard tissues. In particular, the formation processes of minerals can be partly replicated by utilizing bioinspired artificial materials to mimic the functions of biomolecules or stabilize intermediate miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 341 publications
(431 reference statements)
1
71
0
Order By: Relevance
“…Moreover, with significant disadvantages of limited supplies, discomfort at the harvest site, immunogenicity, and transmission of infectious diseases, there is a growing need for developing synthetic grafts for the treatment of damaged or diseased mineralized tissues. , Because of the hierarchical complexity of these mineralized tissues, fabrication of ideal synthetic grafts that can fulfill the requirement is still a challenge for material scientists. Mimicking the biological process to construct these mineralized structures has gained attention in the recent years. A close consideration of the structural composition of bone has revealed that a complex combination of calcium phosphate in the form of the mineral hydroxyapatite, as well as collagenous fibrous proteins, makes up bone and teeth. Bone is a unique tissue with extraordinary mechanical and biological properties due to its intricate nanostructure. , It has been realized that the extracellular matrix, particularly connective tissues with their collagen fibers, is crucial for force transmission and maintenance of the bone structure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with significant disadvantages of limited supplies, discomfort at the harvest site, immunogenicity, and transmission of infectious diseases, there is a growing need for developing synthetic grafts for the treatment of damaged or diseased mineralized tissues. , Because of the hierarchical complexity of these mineralized tissues, fabrication of ideal synthetic grafts that can fulfill the requirement is still a challenge for material scientists. Mimicking the biological process to construct these mineralized structures has gained attention in the recent years. A close consideration of the structural composition of bone has revealed that a complex combination of calcium phosphate in the form of the mineral hydroxyapatite, as well as collagenous fibrous proteins, makes up bone and teeth. Bone is a unique tissue with extraordinary mechanical and biological properties due to its intricate nanostructure. , It has been realized that the extracellular matrix, particularly connective tissues with their collagen fibers, is crucial for force transmission and maintenance of the bone structure.…”
Section: Introductionmentioning
confidence: 99%
“…PILP mineralization methods showcase a promising approach for treating diseases exacerbated by a lack of mineral by delivering amorphous precursors that can subsequently become crystalline HAP in the intrafibrillar compartment of collagen. Most PILP research is on artificial in vitro systems allowing for mechanistic work underpinning how these nanodroplets form, prevent solution mineralization, and direct intrafibrillar mineralization . Importantly, when attempting to create CaP delivery methods for remineralizing craniofacial bones, aspects of the periodontal ligament enthesis, noncollagenous proteins involved in mineral inhibition/nucleation, and cellular contributions will need to be considered.…”
Section: Calcium Phosphate (Cap) Delivery Systems For Craniofacial Bo...mentioning
confidence: 99%
“…Compared with other crystalline CaP phases such as octacalcium phosphate [Ca 8 H 2 (PO 4 ) 6 •5H 2 O] and tricalcium phosphate [Ca 3 (PO 4 ) 2 ], NACPs are widely used in the oral field because of their ability to release large amounts of Ca 2+ and PO 4 3ions (Figure 4) (Iafisco et al, 2018). The amorphous phase strategy is also used by numerous organisms for mineralization, and its advantages can be explained in three ways (Tang et al, 2021). First, the highly hydrated amorphous phase has a liquid-like fluidity and plasticity, considered the basis for constructing complex minerals, especially in extremely small compartments (Athanasiadou Carneiro, 2021).…”
Section: Role Of Amorphous Nanoprecursorsmentioning
confidence: 99%